Differentiation Between Wines According to Geographical Regions in the Western Cape (South Africa) Using Multivariate Analyses Based on Selected Chemical Parameters in Young Red Wines - Minnaar, P.P.; Booyse, M. (South African Journal of Enology and Viticulture, 2017)
The aim of this study was to differentiate between wines of three diverse wine regions, namely the districts Paarl, Stellenbosch and Swartland, in the Western Cape on the basis of chemical parameters, namely pH, volatile acid, total acids, malic acid, lactic acid, glucose, fructose, ethanol and glycerol. A total of 140 young red wines (Pinotage, Cabernet Sauvignon and Merlot) obtained from the 2003 National Young Wine Show were analysed. Classification methods such as stepwise discriminant analysis, canonical discriminant analysis and linear discriminant analysis were applied to the data sets. A total classification of 34.04 % for Cabernet Sauvignon, 42.55 % for Pinotage and 31.25 % for Shiraz was determined. It was concluded that, under the conditions of this study, separation of the wines according to geographical regions was unsuccessful using the selected parameters.